FRI0177 THE ADDITIVE EFFECTS OF HYDROXYCHLOROQUINE TO MAINTENANCE THERAPY WITH STANDARD OF CARE IN PATIENTS WITH SYSTEMIC LUPUS: ERYTHEMATOSUS. (June 2019) - Miyagawa, Ippei; Nakano, Kazuhisa; Nakayamada, Shingo; Iwata, Shigeru; Hanami, Kentaro; Fukuyo, Shunsuke; Kubo, Satoshi; Kawabe, Akio; Miyazaki, Yusuke; Inoue, Yoshino; Ueno, Masanobu; Tanaka, Yoshiya
Abstract : Background: Antimalarial agents such as hydroxychloroquine (HCQ) have long been used as effective therapies for skin and joint symptoms, as well as for the malaise associated with cutaneous lupus erythematosus and systemic lupus erythematosus (SLE). Furthermore, based on the various benefits demonstrated with these agents, the use of antimalarial agents was recently recommended for all patients with SLE. Whereas HCQ has been generally given to most of patients from the beginning of the treatment during the remission-induction therapy in multiple studies, its effects on maintenance therapy have not been sufficiently supported by evidence. Objectives: We evaluated the additive effects of HCQ in maintenance therapy with standard of care (SoC) in 101 patients with SLE for 1 year. Methods: The study included 101 patients diagnosed with SLE, whose course was followed for 1 year at our hospital and affiliated institutions. All patients were receiving maintenance therapy based on the SoC. The primary endpoint was the changes in the SLEDAI. The secondary endpoints were the proportion of emergence of new BILAG A or B organ domain score, and changes in anti-ds DNA Ab titre (U/mL), and serum complement activity (CH50, U/mL) up to year 1, as well as the CS-sparing effect. For these endpoints, the SoC+HCQ group (n = 42) was compared with the SoC group (n = 59) of patients matched for baseline characteristics. The Human Ethics Review Committee of our university reviewed and approved this study. Results: In the SoC+HCQ group, the mean age was 42.2 years, and there were 3 male and 39 female. The mean disease duration was 157.9 months. In the SoC group, the mean age was 43.5 years, and there were 6 male and 53 female. The mean disease duration was 118.9 months. At baseline, no statistically significant differences between the two groups were observed in any baseline characteristics. The SLEDAI improved from 3.07 to 2.28 in the SoC+HCQ group, but significantly deteriorated from 2.73 to 4.8 in the SoC group. The CH50 levels, anti-dsDNA antibody titre, and concomitant CS dose were not significantly changed. The increase in the SLEDAI and concomitant CS dose after 1 year were all significantly greater in the SoC group, and the proportion of patients with SLEDAI flare was significantly lower in the SoC+HCQ group (4.76% vs 25.4%) (SLEDAI flare was defined as an increase of at least four points in the SLEDAI). Regarding the BILAG organ domain, there were no significant differences. SLEDAI flare were observed in 17 patients. When baseline characteristics were compared between patients with and without SLEDAI flare, HCQ was significantly more frequently used in patients without SLEDAI flare. In addition, univariate and multivariate logistic regression analyses were performed to identify the predictive factors for no SLEDAI flare. The univariate logistic analysis identified HCQ use, and immunosuppressant use with a P value of <0.3. Subsequently, multivariate logistic analysis was performed with these factors as dependent variables and identified the presence or absence of HCQ use as a predictive factor (P = 0.0041, odds ratio 6.66, 95% confidence interval 1.73–44.1). The retention rate of HCQ was 90.5%. Conclusion: The comparison between the SoC+HCQ and SoC groups revealed that the addition of HCQ to maintenance therapy with low-dose CS for SLE is safe, and that HCQ was effective, not only for the suppression of disease activity based on the SLEDAI, but also for the prevention of the exacerbation of disease activity. Thus, the present study revealed that HCQ may be a useful mainstay for maintenance therapy based on SoC in patients with SLE. Disclosure of Interests: Ippei Miyagawa: None declared, Kazuhisa Nakano: None declared, Shingo Nakayamada Grant/research support from: Mitsubishi-Tanabe, Takeda, Novartis and MSD, Speakers bureau: Bristol-Myers, Sanofi, Abbvie, Eisai, Eli Lilly, Chugai, Asahi-kasei and Pfizer, Shigeru Iwata: None declared, Kentaro Hanami: None declared, Shunsuke Fukuyo: None declared, Satoshi Kubo Speakers bureau: Bristol-Myers, Pfizer, Takeda, and Eli Lilly, Akio Kawabe: None declared, Yusuke Miyazaki: None declared, Yoshino Inoue: None declared, Masanobu Ueno: None declared, Yoshiya Tanaka Grant/research support from: Abbvie, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eisai, Mitsubishi-Tanabe, MSD, Ono, Taisho-Toyama, Takeda, Speakers bureau: Abbvie, Asahi-kasei, Astellas, Bristol-Myers Squibb, Chugai, Daiichi-Sankyo, Eli Lilly, Eisai, Glaxo-Smithkline, Janssen, Mitsubishi-Tanabe, Novartis, Pfizer Japan Inc, Sanofi, Takeda, UCB, YL Biologics